Peran Mediasi Orang Tua dan Anonimitas terhadap Kecenderungan Cyberbullying Siswa - Santhoso, Fauzan Heru (Jurnal Psikologi, 2019)
This study aimed to determine the role of parental mediation and anonymity towards the tendency of cyberbullying behavior of high school students. This research needs to be done because the tendency of cyberbullying among students is increasing lately. In this study parental mediation and anonymity were predicted to have an influence on cyberbullying tendencies. Therefore the hypothesis in this study was the parental mediation and anonymity can predict cyberbullying tendencies of high school students. The subjects of the study were 159 students of grade XI of state and private high schools in Yogyakarta, with age ranging from 15 to 19 years old, the research subjects were obtained by purposive sampling. Three scales were used in this study, namely the parent mediation scale, the anonymity scale, and the cyberbullying scale. Data analysis used was multiple regression. The results showed that parental mediation and the perception of anonymity had a role in cyberbullying behavior (F = 10.264; df = 2.156; p <0.01). The effective contribution of the two independent variables to the dependent variable was 11.6% with parent mediation variable contributing 5.83% and the perception variable contributing 5.78% to anonymity.